Implementation of Merdeka Curriculum Based on Multicultural in Fiqh Learning: (Case Study at Madrasah Aliyah Darul Ulum II Middle Bujur Batumarmar Pamekasan) - Afandi Afandi; Ach Sayyi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
The application of the Merdeka curriculum in fiqh learning is a form of response to the presence of the era of society 5.0, which invites every individual to continue to develop their potential independently adapted to technological sophistication. The purpose of this study is to examine and study the application of the Merdeka curriculum in fiqh learning. The research method used is a qualitative approach based on phenomenology with the intention of collecting data through observation, interviews, and document studies. Research data obtained through interviews, observation, and document study were then analyzed using Miles and Huberman's interactive analysis techniques. The results of the study show that the implementation of the Merdeka curriculum based on multiculturalism in conceptually learning fiqh in madrasas has formulated fiqh material through integration with the study of classical books (the yellow book). Students are given freedom and flexibility in studying and dissecting various literature that contains the study of fiqh. The structure of the Merdeka curriculum in fiqh learning implemented by this Madrasah is centered on the study of worship fiqh, mu'amalat fiqh, munakahat fiqh, roses fiqh, and jinayat fiqh